2013
DOI: 10.3390/s130506423
|View full text |Cite
|
Sign up to set email alerts
|

Biosensors in Clinical Practice: Focus on Oncohematology

Abstract: Biosensors are devices that are capable of detecting specific biological analytes and converting their presence or concentration into some electrical, thermal, optical or other signal that can be easily analysed. The first biosensor was designed by Clark and Lyons in 1962 as a means of measuring glucose. Since then, much progress has been made and the applications of biosensors are today potentially boundless. This review is limited to their clinical applications, particularly in the field of oncohematology. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 92 publications
0
39
0
Order By: Relevance
“…One of the major advantages of biosensors lies in their versatility, as they can be customized and efficiently used in a wide range of applications [17][18][19][20]. Specifically, biosensors (both re-usable and single-use) are gaining an increasing impact on clinical chemistry and diagnosis [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…One of the major advantages of biosensors lies in their versatility, as they can be customized and efficiently used in a wide range of applications [17][18][19][20]. Specifically, biosensors (both re-usable and single-use) are gaining an increasing impact on clinical chemistry and diagnosis [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…This technology offers advantages such as reduction of time required to complete analysis, simplicity, robustness, reusability, cost-effectiveness and the possibility of miniaturization. Various studies aiming at the application of SPR biosensors in medical diagnostics have been reported [55][56][57]. Cancer morbidity continuous to growth in current society, thus detection of cancer biomarkers is of primary importance.…”
Section: Medical Diagnosticsmentioning
confidence: 99%
“…Development from a temporary to a varying infection of HPV is measured by a robust rise of protein and HPV E6/E7 mRNA presence. The biomarker broadly assessed is p16ink4a, a cyclindependent kinase inhibitor that exists decidedly over conveyed in cancerous plus cervical precancerous tissue [8]. Biosensors are proficient for sensing precise biological analytes as well as varying their existence or concentration into definite, thermal, electrical, optical or else additional signal for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The International Union of Pure and Applied Chemistry expresses a biosensor as, a device that practices biochemical reactions arbitrated by isolated organelles, enzymes or else whole cells to sense the effects of chemical compounds by thermal, optical or electrical signals. Biosensors can be categorized into four classes on the foundation of the kind of transducer used: optical (interferometric, colorimetric, luminescent, and fluorescent) biosensors, mass-grounded piezoelectric as well as acoustic wave biosensors, calorimetric, plus electrochemical (potentiometric, amperometric, and conductometric) biosensors [8].…”
Section: Introductionmentioning
confidence: 99%